2013
DOI: 10.1007/s13353-013-0159-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters for milk urea concentration and milk traits in Polish Holstein-Friesian cows

Abstract: Milk urea concentration (MU) used by dairy producers for management purposes can be affected by selection for milk traits. To assess this problem, genetic parameters for MU in Polish Holstein-Friesian cattle were estimated for the first three lactations. The genetic correlation of MU with milk production traits, lactose percentage, fat to protein ratio (FPR) and somatic cell score (SCS) were computed with two 5-trait random regression test-day models, separately for each lactation. Data used for estimation (15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
26
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 34 publications
(94 reference statements)
10
26
1
1
Order By: Relevance
“…In previous studies with a Brazilian Holstein population from Minas Gerais state, Biassus et al (2011) found values ranging from 0.03 to 0.21 and 0.09 to 0.33 for fat and protein yields, respectively, estimated from random regression models. Rzewuska & Strabel (2013) and Abdullahpour et al (2013) reported very close average heritability values from 0.17 to 0.22, and 0.14 to 0.23, for fat and protein yields, respectively. Trajectories of permanent environmental variances of test-day fat and protein yields were quite constant between 30 and 240 days in milk, in all models, and coincided with the highest heritability of test-day yields in mid-lactation.…”
Section: Resultsmentioning
confidence: 85%
“…In previous studies with a Brazilian Holstein population from Minas Gerais state, Biassus et al (2011) found values ranging from 0.03 to 0.21 and 0.09 to 0.33 for fat and protein yields, respectively, estimated from random regression models. Rzewuska & Strabel (2013) and Abdullahpour et al (2013) reported very close average heritability values from 0.17 to 0.22, and 0.14 to 0.23, for fat and protein yields, respectively. Trajectories of permanent environmental variances of test-day fat and protein yields were quite constant between 30 and 240 days in milk, in all models, and coincided with the highest heritability of test-day yields in mid-lactation.…”
Section: Resultsmentioning
confidence: 85%
“…The genetic parameters obtained in statistical analysis did not differ from those obtained in big population of Polish H-F dairy cattle (Rzewuska & Strabel, 2013). This means that despite the small number of animals included in the analysis the results are not biased with big errors.…”
Section: Resultsmentioning
confidence: 60%
“…According to Křížová et al (2013), the concentration of nitrogen fractions decreased during summer, while during winter it was higher (P <0.05). Rzewuska and Strabel (2013a) reported the association between the sampling month, air temperature, and MU. MU was high during the period from May to October, and the highest values were recorded in the summer months.…”
Section: Resultsmentioning
confidence: 99%
“…Genetic correlation indices (r g ) showed that the urea content in milk was negatively correlated with milk yield (r g = −0.097), positively correlated with fat content (r g = 0.140) and dry matter (r g = 0.125), and very weakly correlated with protein (r g = 0.038) and lactose content (r g = 0.071) ( Table 4). Rzewuska and Strabel (2013a) reported that the average daily heritabilities of MU were 0.22 for the first and 0.21 for the second and third lactations. Hossein-Zadeh and Ardalan (2011) reported that the average genetic correlation for MUN and lactose percentage was close to zero (−0.01), while the average genetic correlation was moderately positive for milk yield (0.24), net energy concentration of milk (0.31), fat (0.21), and protein percentage (0.30).…”
Section: Resultsmentioning
confidence: 99%